Bevacizumab Combined with S-1 and Raltitrexed for Patients with Metastatic Colorectal Cancer Refractory to Standard Therapies: A Phase II Study. (30th April 2021) - Chen, Ye; Zhou, Yu-Wen; Cheng, Ke; Li, Zhi-Ping; Luo, De-Yun; Qiu, Meng; Li, Qiu; Wang, Xin; Shen, Ya-Li; Cao, Dan; Yang, Yu; Bi, Feng; et al.
Abstract : Lessons Learned : Bevacizumab combined with S-1 and raltitrexed demonstrated positive antitumor efficacy and acceptable toxicity. This combination might represent a treatment option for refractory metastatic colorectal cancer. Background: In patients with metastatic colorectal cancer (mCRC) refractory to standard therapies, S-1 plus raltitrexed showed a good objective response rate (ORR) and significant survival benefit in our previous study. In the present study, we assessed the activity and safety of bevacizumab combined with S-1 and raltitrexed. Methods: This investigator-initiated, open-label, single-arm, phase II trial was performed at West China Hospital in China. Patients with mCRC who had disease progression after fluoropyrimidine, irinotecan, and oxaliplatin and had at least one measurable lesion were eligible for this trial. Anti–epidermal growth factor receptor (EGFR) (for tumors with wild-type RAS ) and anti–vascular endothelial growth factor (VEGF) therapy in the first or second line was allowed, but patients who had been treated with bevacizumab across two consecutive chemotherapy regimens were excluded. Patients received bevacizumab (7.5 mg/kg on day 1), oral S-1 (80–120 mg per day for 14 days), and raltitrexed (3 mg/m 2 on day 1) every 3 weeks. The primary endpoint was ORR. Secondary endpoints included progression-free survival (PFS), overall survival (OS), and toxicity. Results: From September 2015 to November 2019, 44 patients were enrolled. Tumor response evaluation was available in 44 patients at the time of the analysis. There were no complete responses; the ORR was 15.9%, and the disease control rate was 54.5%. Median PFS and OS were 110 days (95% confidence interval [CI], 65.0–155.0) and 367 days (95% CI, 310.4–423.6), respectively. The combination was well tolerated. Conclusion: Bevacizumab combined with S-1 and raltitrexed showed promising antitumor activity and safety in refractory mCRC.